Development of Local Culture Based Learning Tools in Sangkakala PAUD Parmaksian District - Rammen Andino Sinaga; Lustani Samosir; Simion D. Harianja (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to develop PAK (Christian Religious Education) Learning Tools Based on Local Culture in PAUD Sangkakala, Parmaksian District. This research is a type of development research or research and development (R&D). Data is described quantitatively which seeks to develop viable and effective products that are used in learning. The product developed in this research is a learning plan based on local Toba Batak culture and its evaluation. The theory referred to in this development research is the ADDIE development model with the following stages: 1) Analysis, 2) Design, 3) Development, 4) Implementation and 5) Evaluation. The results of the research are as follows: 1) Sangkakala PAID Teachers in Parmaksian District need local culture-based PAK learning tools, 2) The model developed begins with compiling 4 RPH (Daily Implementation Plans), media and learning evaluations based on local Toba Batak culture, 3) Based on the validation results of the revised model are suitable for use. 4) The results of implementation and evaluation show that learning tools can be used effectively and efficiently at the age of 4-5 years.